Dynamic Changes of Serum Heart Type-Fatty Acid Binding Protein in Cancer Patients Treated With Immune Checkpoint Inhibitors - Yuan, Ming; Zang, Li; Xu, Aiqing; Gong, Mengqi; Liu, Qing; Huo, Bin; Wang, Jinhuan; Fu, Huaying; Tse, Gary; Roever, Leonardo; Li, Guangping; Wang, Haitao; et al. (Frontiers in Pharmacology, 2021)
Objective: Immune checkpoint inhibitors (ICIs) are effective anti-cancer drugs that can improve survival in cancer patients, but their use may be associated with adverse cardiovascular side effects. Therefore, there is a clinical unmet need to identify non-invasive biomarker to detect subclinical cardiac toxicity after ICI treatment. The aim of this study is to examine the plasma levels of biomarkers in cancer survivors who were treated with ICIs. Patients and Methods: In a cohort of 19 cancer patients, biomarkers were evaluated at baseline, 1 month, 3 and 6 months after ICI administration. These biomarkers, hypothesized to be mechanistically relevant to cardiotoxicity, included cardiac troponin I (cTnI), high-sensitivity C-reactive protein (Hs-CRP), N-terminal pro–B-type natriuretic peptide (NT-pro BNP), CK (creatine kinase), CK-MB (creatine kinase-MB), Pentraxin-related protein 3 (PTX3), growth differentiation factor 15 (GDF-15), heart type-fatty acid binding protein (H-FABP) and galectin 3 (Gal-3). Results: H-FABP, but not other biomarkers, were increased at 3 months, which persisted at 6 months (529.28 ± 312.83 vs. 752.33 ± 283.65 vs. 808.00 ± 289.69 pg/ml, p = 0.031 and p = 0.013). Left ventricular ejection fraction (63.00 ± 4.15% vs. 63.74 ± 4.07%, p > 0.05) was not significantly reduced at this time point. Conclusions: H-FABP, but not other biomarkers, were increased in patients who were treated using ICIs. H-FABP might be a more sensitive biomarker to detect ICI-related subclinical myocardial damage than traditional cardiac biomarkers.